A linguagem-imagem em João Gilberto Noll - Souza, Eliane Lage (2007)
Based on the concepts about the image studied since antiquity until nowadays, the actual dissertation analyses some textual creations of João Gilberto Noll which transform the language into a visual practice denoting correspondences between text and image. This process takes place under two aspects: the first one, tries to interlace literature and cinema, verifyng if the narrative procedures used by the writer has something to do with cinematographic language. The second, has the intention of studying the appropriation of the movie techniques in the composition of the fictional writing, what would prove the choice of Noll texts for the cinema. Analysing this proposal it is possible to prove that there is fact in the narrative of the author a poetical image.